Analisis Pelaksanaan Pelayanan Kesehatan Perorangan (UKP) Di Puskesmas Sebelum dan Selama Pandemi Covid-19: Literature Review - Havida Aini Fauziyah; Inge Dhamanti (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
The Covid-19 pandemic has an impact on health services, where there is a change in providing services to the community in order to avoid Covid-19 transmission in health service facilities. Therefore, this study aims to find out the changes carried out by public health center in providing individual health services, including outpatient, inpatient and delivery, emergency, pharmacy service, laboratory service, referral system, and funeral services. The method used in this study was a literature review. The type of review was narrative review, where the researcher looked for reference sources through policies, laws and regulations, guide book, or technical instructions regarding individual health services in Puskesmas before and during the Covid-19 pandemic. The study found some changes carried out including the application of triage/screening for every visitor, the application of physical distancing, changes in service flow, patient seating arrangement, use of transparent screen. Moreover, there was a modification of service schedule, the limitation of dental polyclinic service, and the utilization of information and communication systems in providing health services during the Covid-19 pandemic. Changes made by public health centers in the provision of individual health services are part of an effort to prevent and control the spread of Covid-19 infection on health services.